2023
DOI: 10.1182/bloodadvances.2022007340
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced VWF clearance in low VWF pathogenesis: limitations of the VWFpp/VWF:Ag ratio and clinical significance

Abstract: Increased von Willebrand factor (VWF) clearance plays a key role in the pathogenesis of Type 1 and Type 2 von Willebrand disease (VWD). However, the pathological mechanisms involved in patients with mild to moderate reductions in plasma VWF:Ag (30-50 IU/dL range; Low VWF) remain poorly understood. In this study, we investigated the hypothesis that enhanced VWF clearance may contribute to Low VWF pathobiology. Low VWF patients were recruited to the LoVIC study following ethical approval and informed consent. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…Furthermore, VWFpp clearance kinetics may also vary between individual patients with low VWF and type 1 VWD. 50 Taken together, these data demonstrate that enhanced VWF clearance plays an important role in low VWF pathogenesis. Although the biological mechanisms responsible for pathological VWF clearance in patients without VWF sequence variants has not been defined, previous studies have reported altered VWF glycosylation in subsets of patients with both low VWF and type 1 VWD, respectively.…”
Section: Low Vwf and Type 1 Vwdmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, VWFpp clearance kinetics may also vary between individual patients with low VWF and type 1 VWD. 50 Taken together, these data demonstrate that enhanced VWF clearance plays an important role in low VWF pathogenesis. Although the biological mechanisms responsible for pathological VWF clearance in patients without VWF sequence variants has not been defined, previous studies have reported altered VWF glycosylation in subsets of patients with both low VWF and type 1 VWD, respectively.…”
Section: Low Vwf and Type 1 Vwdmentioning
confidence: 59%
“…47,48 Interestingly, Doherty et al recently reported that the sensitivity of the steady-state VWFpp/VWF:Ag ratio for identifying increased VWF clearance in patients with low VWF was significantly reduced compared to gold-standard desmopressin fall-off rates. 50 This likely reflects the fact that the reduction in plasma VWF half-life in low VWF patients ($6 hours) is not as marked as that observed in type 1C patients (2$4 hours). Furthermore, VWFpp clearance kinetics may also vary between individual patients with low VWF and type 1 VWD.…”
Section: Vwf Clearance In Low Vwfmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, a higher proportion of patients with type 1 were found to have abnormal VWFpp:VWF:Ag ratios, suggesting that VWD type 1C may be more common than previously suspected. 64 65…”
Section: Vwf Multimer Patternsmentioning
confidence: 99%